Harvesting energy from real human urine in a photo-microfluidic fuel cell using TiO2–Ni anode electrode. (26th July 2021) - Dector, D.; Ortega-Díaz, D.; Olivares-Ramírez, J.M.; Dector, A.; Pérez-Bueno, J.J.; Fernández, D.; Amaya-Cruz, D.M.; Reyes-Rojas, A.
Abstract: The use of a liquid sample employed for analysis in microfluidic fuel cells has been increased because it can be used in order to obtain medical diagnostic and at the same time as fuel. This document presents the construction and evaluation of a photo-assisted microfluidic fuel cell (photo-μFC) that uses human urine as a fuel. For the construction of this photo-μFC, TiO2 nanoparticles modified with Ni(OH)2 were synthesized for use as a photoanode in the oxidation of the urea content in urine, finding an increase in the absorption of light in the visible spectrum with respect to TiO2 . Nanoparticles of TiO2 –Ni in a mixture of anatase (60%) and brookite (40%) phases were found with crystallite sizes of 9 and 15 nm, respectively. The photo-μFC proved with urine, showed an open-circuit potential of 0.70 V, a maximum current density of 1.7 mA cm −2 and a maximum power density of 0.09 mW cm −2 . The photo-μFC developed was evaluated for 15 consecutive hours at room temperature to observe the lifetime and stability of the photoanode with respect to the generated current. In addition, the oxidation of the urea by the photogenerated holes (h + ) in the TiO2 was verified. This research shows the novelty of a promising advance in the use of a microfluidic fuel cell operated with a single-stream from human urine and using photoanodes (TiO2 –Ni) to obtain electrical power with a feasible application in low power portable medical devices. Graphical abstract: Image 1 Highlights: Human urine is used as fuel to generate electrical power. An OCP of 0.7 V and a maximum current density of 1.7 mA cm −2 are achieved. Oxidation of the urea by the photogenerated holes was verified. Photo-μFC developed was evaluated for 15 consecutive hours at room temperature.